Realistic computer simulation of bolus flow during swallowing - Michiwaki, Yukihiro; Kamiya, Tetsu; Kikuchi, Takahiro; Toyama, Yoshio; Takai, Megumi; Hanyu, Keigo; Inoue, Motoki; Yahiro, Nobutaka; Koshizuka, Seiichi (Food hydrocolloids, 2020)
In this study, swallow simulation, Swallow Vision ®, was used to estimate the velocity, shear rate, and viscosity of food during swallowing. The subjects were a healthy young person and an elderly patient with aspiration. The test food was a Newtonian fluid (viscosity 2.5 mPa･ s) and a non-Newtonian fluid (viscosity 300 mPa･s at a shear rate of 50 [1/s]). A realistic numerical organ model was created based on Computed Tomography and Video-fluorography while swallowing the test food, and the bolus flow was analyzed using a numerical model whose validation was evaluated. Consequently, in the analysis of a model in which a healthy person swallowed the Newtonian fluid, the median velocity of the bolus flow changed in the range of 0.2–0.6 m/s, and there was a bimodal peak. The median shear rate ranged from 75 to 200 [1/s], and there were three peaks. In the swallowing of the non-Newtonian fluid, the flow velocity smoothly changed between 0.1 and 0.5 m/s, the shear rate varied between 50 and 100 [1/s], and the average of the median values during the entire swallowing process was 78 [1/s]. The trajectory analysis of the simulation model of the dysphagia patient demonstrated that the aspirated particles flowed faster than the non-aspirated particles. These results indicate that the numerical simulation based on medical images can analyze the bolus flow during swallowing, although there are still issues to be solved. Although the Newtonian fluid particles change their shear rate with time, the most frequent shear rate is approximately 100 [1/s]. Particle having the most frequent shear rate are quite a few about 100 in number. Consequently, the frequency distribution of the shear rate is constantly wide.In the non-Newtonian fluid, the frequency distribution has a sharp peak, approximately 75 [1/s] of shear rate, where more than 200 particles gather. Consequently, the frequency distribution spreads to an area narrower than that of the Newtonian fluid. [Display omitted] •Computer simulation estimated velocity, shear rate, and viscosity during swallowing.•A Newtonian fluid velocity change had two peak values.•A shear rate of a non-Newtonian fluid changed as the swallowing process proceeded.